2020
DOI: 10.3390/ijerph17186897
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Children with Visual Impairments during Different Segments of the School Day

Abstract: Schools provide opportunities for children with visual impairments (VI) to accumulate recommended daily moderate-to-vigorous-intensity physical activity (MVPA). This study aimed to determine physical activity (PA) across the school day among special school children with VI in China. The study objectively measured the MVPA levels of children with VI during the recess, lunchtime, physical education (PE) classes, before-school, and after-school periods segments on PE days and non-PE days. Moreover, this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…For instance, familial trials were conducted to correlate PA between VI, their parents, and siblings [ 66 ]. While in [ 65 ], the authors studied the PA of children with VI during different segments of the school day from the special school for VI in Xingqing Districts in Yinchuan, China. In this trial, a total of 600 min acceleration was recorded per day, and this input was analyzed within the ActiLife Lifestyle Monitoring System from Actigraph.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, familial trials were conducted to correlate PA between VI, their parents, and siblings [ 66 ]. While in [ 65 ], the authors studied the PA of children with VI during different segments of the school day from the special school for VI in Xingqing Districts in Yinchuan, China. In this trial, a total of 600 min acceleration was recorded per day, and this input was analyzed within the ActiLife Lifestyle Monitoring System from Actigraph.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently used accelerometers included ActiGraph from Actigraph Corp, ADXL from Analog Devices, and KXR from Kionincs. Identify human movement ADXL345 RGB Camera, Ultrasonic Sensor [59] Measures physical activity ActiGraph GT3x N/A [60] Measures physical activity ActiGraph wGT3X-BT N/A [61] Measures physical activity ActiGraph wGT3X-BT N/A [62] Measures physical activity ActiGraph wGT3x+ N/A [63] Sense the foot movements KXR94-2050 N/A [64] Measures physical activity ActiGraph GT3x N/A [65] Measures physical activity ActiGraph GT3x N/A [66] Monitoring of human activities Not specified N/A [67] The Actigraph Corp wearable accelerometers were used in many clinical trials found in the systematic review. The accelerometers were used to measure PA within the VI community, with a major experimental focus on kids and older adults [60][61][62].…”
Section: Accelerometermentioning
confidence: 99%
“…Teachers and parents of children with disabilities in China focus more on their well‐being, living skills, physical improvements and career planning than academic performance (Qi et al . 2020), which substantially reduces their academic pressure and therefore increases the likelihood of meeting sleep guidelines. Furthermore, this study excluded students with ID who are currently taking medications for sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…After that stage, detectable at about the age of eight, a vicious spiral of physical activity disengagement onsets in children showing low motor competence ( 100 103 ). Literature has frequently reported that VI children and adolescents, when compared to sighted peers, tend to conduct a more sedentary life and to exhibit lower physical fitness ( 20 , 31 , 62 , 104 108 ). This latter, along with a coherent motor skills impairment, seems to arise mostly from low participation in physical and after-school sport activities ( 37 , 94 , 109 – 111 ).…”
Section: Adapted Physical Activity Benefits On Balance Control In Vis...mentioning
confidence: 99%